Nanopartículas de Pt-TiO2 com propriedades catalíticas e fotocatalíticas - Rabelo, Adriano Cesar (Universidade Federal de São Carlos, 2013)
In the first part of this work, a binary system composed of TiO2 and Pt particles was used as photocatalyst for degradation of methyl orange under different lighting conditions: simulated sunlight and ultraviolet. In these experiments, the photodegradation over the composite Pt-TiO2 did not show an increase in their activities compared to pure TiO2. Moreover, during the experiments, a rapid loss of color was observed when Pt-TiO2 was employed before the reaction to be illuminated. The analysis of UV-Vis spectrum showed that one band at 304 nm increased and then remained constant. This caught our attention and was the object of study and the second part of the work. In the second part, catalysis experiments for methyl orange reaction were performed using Pt-TiO2 and pure Pt in the absence of light. The reaction was followed by UV-Vis spectroscopy and by high performance liquid chromatography coupled to a mass spectrometer. The reaction products were identified as their kinetics of formation. Analyzing the data, we conclude that the same reaction is occurring when pure Pt or the composite was employed. The main difference in the reaction rates is that to composite it was 266 times greater. The rate constant was standardized in different ways to exclude effects of the platinum amount and surface area. The smaller of mass and area normalized value was 12 times higher for the composite. The quantity of Pt used was varied in the composite and maximum reaction rate occurs when the Pt molar percentage was 20%. The presence of a peak at catalytic activity when the Pt mass is altered demonstrates the involvement of both materials in the process.
Pt-TiO2 nanoparticles with catalytic and photocatalytic properties
Keywords: Catálise; Fotocatálise; Corantes; Metila; Platina; Óxido de titânio; CIENCIAS EXATAS E DA TERRA::QUIMICA